A review on natural fiber reinforced polymer composites (NFRPC) for sustainable industrial applications - Siti Hasnah, Kamarudin; Mohd Salahuddin, Mohd Basri; Rayung, Marwah; Falah, Abu; So’bah, Ahmad; Mohd Nurazzi, Norizan; Syaiful, Osman; Norshahida, Sarifuddin; Mohd Shaiful Zaidi, Mat Desa; Ummi Hani, Abdullah; Intan Syafinaz, Mohamed Amin Tawakkal; Luqman Chuah, Abdullah (MDPI, 2022)
The depletion of petroleum-based resources and the adverse environmental problems, such as pollution, have stimulated considerable interest in the development of environmentally sustainable materials, which are composed of natural fiber–reinforced polymer composites. These materials could be tailored for a broad range of sustainable industrial applications with new surface functionalities. However, there are several challenges and drawbacks, such as composites processing production and fiber/matrix adhesion, that need to be addressed and overcome. This review could provide an overview of the technological challenges, processing techniques, characterization, properties, and potential applications of NFRPC for sustainable industrial applications. Interestingly, a roadmap for NFRPC to move into Industry 4.0 was highlighted in this review.